Determinants of foreign direct investment in Asia - Wong, Yi Hui (2020)
Foreign direct investment (FDI) is a widely discuss topic in recent years. Countries rely on FDI to stimulate the economic growth, reduce unemployment rate, develop quality infrastructure and stimulate transfer of advance technology and knowledge from developed countries. Hence, this dissertation tends to examine the determinants of FDI in Asia.